2008
DOI: 10.1103/physrevb.77.165334
|View full text |Cite
|
Sign up to set email alerts
|

Electronic transport in modulation-doped InSb quantum well heterostructures

Abstract: The mobility and carrier concentration of a number of InSb-based modulation-doped quantum well heterostructures are examined over a range of temperatures between 4.5 and 300 K. Wide well ͑30 nm͒ and narrow well ͑15 nm͒ structures are measured. The temperature dependent mobilities are considered within a scattering model that incorporates polar optical and acoustic phonon scatterings, interface roughness scattering, and scattering from charged impurities both in the three-dimensional background and within a dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 29 publications
4
59
0
1
Order By: Relevance
“…In this way, subsequent growth of InSb QWs with high mobilities is achieved with remote delta doping (in the range 10-40 m 2 /Vs at 2 K and 4-6 m 2 /Vs at 300 K). 8,9,21,22 Here, we study the electronic properties of two sets of modulation doped InSb/Al x In 1-x Sb QW heterostructures grown by molecular beam epitaxy onto semi-insulating GaAs undoped spacer layer. The two MBL samples differ from each other only in top cap thickness and Te-doping density (fixed spacer thickness) with MBL-2 having a thinner top cap with a nominally higher doping density than MBL-1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this way, subsequent growth of InSb QWs with high mobilities is achieved with remote delta doping (in the range 10-40 m 2 /Vs at 2 K and 4-6 m 2 /Vs at 300 K). 8,9,21,22 Here, we study the electronic properties of two sets of modulation doped InSb/Al x In 1-x Sb QW heterostructures grown by molecular beam epitaxy onto semi-insulating GaAs undoped spacer layer. The two MBL samples differ from each other only in top cap thickness and Te-doping density (fixed spacer thickness) with MBL-2 having a thinner top cap with a nominally higher doping density than MBL-1.…”
Section: Methodsmentioning
confidence: 99%
“…21,42 For narrow 15-nm InSb QWs, mobilities are typically lower (7-11 m 2 /Vs at 2 K), and it was found that interface roughness scattering adds a significant contribution to the total scattering rate. 42 It follows that interface roughness scattering may also play a role in our samples. A second effect is also relevant.…”
Section: A Low-temperature Transportmentioning
confidence: 99%
See 2 more Smart Citations
“…4 This novel material is the subject of numerous experimental studies of transport, optical, magneto-optical, and spin-related phenomena. [1][2][3][4][5][6][7][8][9][10][11][12][13][14] The characteristics driving the interest in this novel narrow gap material are the high carrier mobility, small effective masses, large Landé g * factor, possibility of the mesoscopic spindependent ballistic transport, and a strong spin-orbit coupling. The latter gives rise to a number of optoelectronic effects such as, e.g., terahertz photoconductivity 15 and the circular photogalvanic effect [16][17][18][19][20][21][22] recently observed in InSb QWs.…”
Section: Introductionmentioning
confidence: 99%